The Influence of Internal Audit, Capital Structure, Independent Board of Commissioners and Institutional Ownership on the Financial Performance of Banking Sector Companies Listed on the IDX for the 2018-2020 Period - Ulfa Khairunnisa; Helmi Yazid; Iis Ismawati (Journal of Applied Business, Taxation and Economics Research, 2022)
The purpose of this study was to determine whether Internal Audit, Capital Structure, Board of Commissioners, and Institutional Ownership have a significant effect on the financial performance of banking companies listed on the Indonesia Stock Exchange. This research uses quantitative methods. The sampling technique used purposive sampling and obtained as many as 9 companies. The population in this study are banks listed on the IDX. The analytical method used in this research is multiple linear regression analysis method. The data processing process uses SPSS 22. From the results of this study, all of the banking sector companies that are sampled generate profits by using research assets; the average number of internal audit members in the banking sector is 4; Companies in the banking sector in using their capital structure are still larger from sources of debt than their own capital; the company has the support to provide supervision on the company's performance; Relatively high institutional ownership.